2013
DOI: 10.5137/1019-5149.jtn.8710-13.1
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bilateral decompression via unilateral approach and classic laminectomy in patients with spinal stenosis

Abstract: AIm: Bilateral decompression via unilateral approach is one of the minimally invasive methods used for degenerative spinal stenosis. The aim of this retrospective study was to observe the clinical and radiological results of classic laminectomy and bilateral decompression via unilateral approach applied for lumbar stenosis. mATERIAl and mEThods:The data of 40 patients who underwent surgical treatment for lumbar spinal stenosis with different techniques was reviewed retrospectively. The patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Cavuşoğlu et al (14) found the patient's satisfaction rate to be 94% and the recovery rate to be 96% during the 18-24-month follow-up periods of patients with BDUA. In their study comparing clinical and radiological results of BDUA and classical laminectomy, Yaman et al (15) found differences in VAS scores of leg pain in the postoperative 6 th and 12 th months. However, low back pain VAS scores in patients with BDUA were found to be significantly lower.…”
Section: Discussionmentioning
confidence: 98%
“…Cavuşoğlu et al (14) found the patient's satisfaction rate to be 94% and the recovery rate to be 96% during the 18-24-month follow-up periods of patients with BDUA. In their study comparing clinical and radiological results of BDUA and classical laminectomy, Yaman et al (15) found differences in VAS scores of leg pain in the postoperative 6 th and 12 th months. However, low back pain VAS scores in patients with BDUA were found to be significantly lower.…”
Section: Discussionmentioning
confidence: 98%
“…This technique incorporates a midline incision, opening the fascia, retracting the muscles, hemilaminectomy, bilateral flavectomy, and decompression (5,18). Since BDUA has several advantages such as less blood loss, a shorter stay in hospital, lower complication rates, and less traumatization of surrounding tissues, it has been increasingly applied by neurosurgeons for the treatment of LSS over the past two decades (1,4,13,14,16,19,22). However, this technique has some disadvantages such as accidental dural tears, root…”
Section: █ Discussionmentioning
confidence: 99%
“…Machado et al reviewed different surgical methods for decompression and widening the spinal canal in LSS and reported that decompression plus fusion, or expanding the interspinous process spaces was not superior to conventional decompression alone (12,17). Many current articles have suggested the avoidance of bilateral laminectomy and instrumentation because bilateral decompression with a unilateral approach (BDUA) has been shown to be effective in reducing pain, increasing walking distance, and improving disability (1,13,14,16,19,22). However, some reports have demonstrated that although unilateral laminectomy is effective in the early postoperative period, it has poor outcomes in the long term (approximately 5 years) (6,10).…”
Section: █ Introductionmentioning
confidence: 99%
“…Many minimally invasive methods have been developed with rapidly increasing use to overcome this condition (7,14). The most important of these methods is bilateral decompression with a unilateral approach (15). However, in order to perform decompression on the side with facet joint hypertrophy, the facet joints must still be shaved.…”
Section: █ Discussionmentioning
confidence: 99%